2009
DOI: 10.1007/s11090-009-9209-8
|View full text |Cite
|
Sign up to set email alerts
|

Methane Conversion: a Case Study for Simplification of Plasma Chemistry Models by the Omission of Charged Species

Abstract: In this study the possibility of the simplification of plasma chemistry models was investigated in methane thermal plasma. Although, ionic species and electrons are important compounds of plasmas, their concentrations are much lower than of the neutral species. The role of non-neutral species, ions and electrons was investigated for a 1 v% methane-99 v% argon mixture by comparing the model concentration outputs obtained by thermodynamic and kinetic models and also by two thermodynamic models with and without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In arc discharge, the mixture of neutral and ionic species is at thermal equilibrium. Kovács et al [59] have demonstrated that at a temperature higher that 4000K the reactivity of ionic species is considerably lower than that of neutral species. Therefore, the decomposition of methane is driven by thermal activation because high temperature provides sufficient energy for the activation of the dehydrogenation reaction.…”
Section: Plasma Chemistry For Thermal Plasmamentioning
confidence: 99%
“…In arc discharge, the mixture of neutral and ionic species is at thermal equilibrium. Kovács et al [59] have demonstrated that at a temperature higher that 4000K the reactivity of ionic species is considerably lower than that of neutral species. Therefore, the decomposition of methane is driven by thermal activation because high temperature provides sufficient energy for the activation of the dehydrogenation reaction.…”
Section: Plasma Chemistry For Thermal Plasmamentioning
confidence: 99%
“…Arrhenius parameters were adopted from the NIST database [23], while there for the reverse reactions they were calculated by the MECHMOD [24]. In the mechanismdue to the low concentrations of the ionic species and the small reaction rates, no ionic species were considered [25].…”
Section: Simulationsmentioning
confidence: 99%
“…In the thermal plasma environment, chemically active species can be generated through a combination of thermal activation and electron collisions [55]. However, Kovács et al [56] indicated that, in thermal plasma, the reactivity of ionic species is significantly lower compared to neutral species (a result of their low concentration). Consequently, the decomposition of methane is primarily governed by thermal activation, wherein the high energy initiates the dehydrogenation reaction per Equations ( 10)-( 13).…”
Section: Methane Pyrolysis Mapping For Graphene Productionmentioning
confidence: 99%